Relation Between Energy Intake and Obesity or Overweight in Childbearing Age Woman: A Scoping Review - Tri Siswati; Az Zahra Nur Ainiyyah; Hasna Afifah; Almira Sitasari (Medsci Publications, 2024)
Background: Obesity is a problem that affects public health all over the world, and the prevalence of obesity among women is twice as high as it is among males. The objective is to discuss the prevalence of obesity or overweight among women of reproductive age. Methods: We use a scoping review method using academic journals published from 2018 to 2023. The literature was searched using electronic databases Google Scholar and PubMed. We make use of the following search terms: overweight or obesity, prevalence or incidence, childbearing age or early adulthood, and either Indonesia or Asian. A total of 173 research was identified and 9 research was included in this review. Results: The study highlights the link between dietary patterns, particularly fast food, and obesity among childbearing age women. It emphasizes the importance of maternal dietary choices in young adulthood to reduce maternal obesity, hypertension, and CVD. Combining these parameters can provide a more comprehensive assessment. Conclusions: Food selection is crucial for women and young adults to prevent obesity and NCDs, requiring education, awareness campaigns, maternal health support, and early intervention, especially in low-income countries.